The Role of the Mandar Diaspora in South Kalimantan in Establishing Indonesian’s Maritime Network, 1970s – 2000s - Hamid, Abd Rahman; Idham, Idham; Lamijo, Lamijo; Nensia, Nensia; Hamsiati, Hamsiati; Azis, Muhammad Nur Ichsan (Paramita: Historical Studies Journal, 2024)
Abstract: This article explains the role of the Mandar diaspora in South Kalimantan in establishing Indonesia's maritime network from the 1970s to the 2000s. The data used in this study consists of oral history sources from the actors obtained through in-depth interviews, supplemented by relevant literature. This study has three research questions: what were the driving forces of Mandar people becoming diaspora in South Kalimantan, how did the Mandar diaspora sailors  build their  maritime networks, and how did they respond  towards the modernization of shipping? The research findings indicate that the triggering factors for the migration of the Mandar people to South Kalimantan were the compulsory labor policy in the 1930s and security disturbances in the 1950s in Sulawesi. Additionally, this migration was supported by the geohistorical factors of South Kalimantan in the history of Mandar navigation. The Mandar diaspora in South Kalimantan successfully rebuilt the maritime network with Sulawesi and Java in transporting copra. The maritime network of the Mandar diaspora expanded in the 1970s after the modernization of shipping and joint partnerships with Chinese, Banjar, and Bugis traders. As a result, the Mandar diaspora network expanded to include the hinterlands of Merauke (Papua). By understanding the Mandar diaspora in South Kalimantan, this research makes a significant contribution to understanding the role of the Mandar people in building the maritime network and simultaneously strengthening their identity as a maritime ethnic group in Indonesia. Abstrak: Artikel ini menjelaskan tentang peran diaspora Mandar di Kalimantan Selatan dalam membangun jaringan maritim Indonesia sejak tahun 1970an-2000an. Data yang digunakan dalam riset ini adalah sumber sejarah lisan dari pelaku yang diperoleh lewat wawancara mendalam dan ditambah bahan pustaka yang relevan. Ada tiga persoalan yang dijawab di sini yaitu:  bagaimana dan mengapa orang Mandar menjadi diaspora di Kalimantan Selatan, bagaimana usaha pelaut diaspora Mandar membangun jaringan maritimnya, dan bagaimana bentuk respon mereka terhadap modernisasi pelayaran. Hasil penelitian menemukan bahwa faktor pemicu terjadinya migrasi orang Mandar ke Kalimantan Selatan adalah adanya  kebijakan wajib kerja paksa pada 1930an dan gangguan keamanan 1950an di Sulawesi. Selain itu juga didukung oleh faktor geohistoris Kalimantan Selatan dalam sejarah pelayaran orang Mandar. Diaspora Mandar di Kalimantan Selatan berhasil membangun kembali jaringan maritim dengan Sulawesi dan Jawa dalam pengangkutan kopra. Jaringan maritim diaspora Mandar berkembang pada 1970an setelah modernisasi pelayaran dan joint partner dengan pedagang Cina, Banjar, dan Bugis. Hasilnya, jaringan diaspora Mandar bertambah luas hingga mencakup pedalaman Merauke (Papua). Dengan memahami diaspora orang Mandar di Kalimantan Selatan, penelitian ini berkontribusi penting untuk memahami peran orang Mandar dalam membangun jaringan maritim dan sekaligus mengukuhkan jati dirinya sebagai sukubangsa bahari Indonesia.